2021
DOI: 10.3390/foods10061322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inclusion of Schizochytrium spp. and Forage-to-Concentrate Ratios on Goats’ Milk Quality and Oxidative Status

Abstract: Although the dietary inclusion level of polyunsaturated fatty acids (PUFA) and the forage: concentrate (F:C) ratio affect milk quality, their interaction has not been broadly studied. To address such gaps and limitations a two-phase trial using twenty-two dairy goats was carried out. During the first phase, both groups (20 HF n = 11; high forage and 20 HG n = 11; high grain) were supplemented with 20 g Schizochytrium spp./goat/day. The 20 HF group consumed a diet with F:C ratio 60:40 and the 20 HG-diet consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Besides, NADPH oxidase also provokes the concentration of O 2 ●− [ 45 ]. Increased SOD activity was also reported in goats’ blood plasma that was fed with high PUFA content [ 46 ]. Furthermore, supplementing whole sesame seeds in goats’ diets [ 47 ], also increased the SOD activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides, NADPH oxidase also provokes the concentration of O 2 ●− [ 45 ]. Increased SOD activity was also reported in goats’ blood plasma that was fed with high PUFA content [ 46 ]. Furthermore, supplementing whole sesame seeds in goats’ diets [ 47 ], also increased the SOD activity.…”
Section: Discussionmentioning
confidence: 91%
“…The reported level of PC in the experimental groups followed the same trend with those of MDA, which further supports the assumption of an oxidative response in the highest studied level of inclusion of Camelina seeds in ewes’ diets. As a matter of fact, a high dose of PUFA in goats’ diets, also resulted in increased MDA and PC levels [ 46 ]. Interestingly, the increased level of PC in the CSS16 group may be associated with the proteins’ oxidative damage by the oxygen-free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The proper achievement of rumen function would depend on temperature and diet composition and affects the ruminants' health and productivity (Mavrommatis et al, 2021b;Phesatcha et al, 2021;Soltan et al, 2021). CAP has been extensively studied as a feed additive for ruminants in vivo (Oh et al, 2015;Castillo-Lopez et al, 2021) and in vitro (Busquet et al, 2006); however, little attention has been paid to its effect on rumen fermentation when the rumen is subjected to physiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Morine et al [ 67 ] reported that the level of H 2 S in the rumen decreased linearly with the upsurge in the dietary roughage neutral detergent fiber (rNDF) content. Overall, the increase of D. desulfuricans may result in an accumulation of hydrogen sulfite in the goats’ rumen, potentially concealing dangerous consequences for animals’ health and performance which may be eliminated by altering the forage-to-concentrate ratio in Schizochytrium spp.-fed goats [ 68 ]. In this context, Schizochytrium spp.…”
Section: Discussionmentioning
confidence: 99%